2007
DOI: 10.1371/journal.pone.0001238
|View full text |Cite
|
Sign up to set email alerts
|

High CO2 Levels Impair Alveolar Epithelial Function Independently of pH

Abstract: BackgroundIn patients with acute respiratory failure, gas exchange is impaired due to the accumulation of fluid in the lung airspaces. This life-threatening syndrome is treated with mechanical ventilation, which is adjusted to maintain gas exchange, but can be associated with the accumulation of carbon dioxide in the lung. Carbon dioxide (CO2) is a by-product of cellular energy utilization and its elimination is affected via alveolar epithelial cells. Signaling pathways sensitive to changes in CO2 levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
135
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 110 publications
(145 citation statements)
references
References 46 publications
7
135
0
3
Order By: Relevance
“…36). The signaling pathways sensitive to changes in CO 2 levels in mammalian non-neuronal cells are incompletely understood (37,38), but in plants and neuronal mammalian cells, many reports have identified conserved signaling pathways (39 -41).…”
Section: Discussionmentioning
confidence: 99%
“…36). The signaling pathways sensitive to changes in CO 2 levels in mammalian non-neuronal cells are incompletely understood (37,38), but in plants and neuronal mammalian cells, many reports have identified conserved signaling pathways (39 -41).…”
Section: Discussionmentioning
confidence: 99%
“…and then injected with insulin. The isolated lung preparation has been previously described (Briva et al, 2007;Myrianthefs et al, 2005;Rutschman et al, 1993;Saldias et al, 2001). Briefly, the lungs and heart were removed en bloc.…”
Section: Isolated Perfused Rat Lung Modelmentioning
confidence: 99%
“…However, more recent studies have suggested that high pCO 2 can cause oxidative stress in the lung, and injury (3). More recently it has been reported that in rat lungs and human epithelial cells, high pCO 2 decreased alveolar fluid clearance independently of pH and ROS (4,5). In some reports it has been shown that CO 2 uptake involves the aquaporin and RH1 channels (6,7).…”
mentioning
confidence: 99%